(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
Our students graduated as media moderators at the University of West Hungary, Benedek Elek Faculty of Pedagogy and finished a high level vocational training in 2013. In my lecture I present and analyse their masterworks. Media moderators can work as editors, interviewers and presenters, as well as event planners and organisers in cultural institutions. According to this, during the course students get to know the special features of creating a media production. Their masterwork was to create a 15–20 minute long radio or television program with the help of a professional consultant. I analyse their master works from the perspective of their genre, topic and the use of language. I am also trying to get an answer on the question how the exact location of this nationwide course influences their work and which communicational solutions and methods they have used in order to transmit the main point of their work.